Scots pine (Pinus sylvestris L.) radial growth dynamics in forest stands in the vicinity of “Akmenes cementas” plant - Stravinskienė, Vida; Erlickytė-Marčiukaitienė, Regina (Journal of Environmental Engineering and Landscape Management, 2009)
Investigation of Scots pine annual radial increment was carried out in the surroundings of one of the largest pollution sources in Lithuania – the cement plant “Akmenes cementas”. The main objective of the investigation was to analyse possible impact of climatic and anthropogenic factors on the radial growth of Scots pine (Pinus sylvestris L.) stands growing in the local impact zone of the plant. Investigation has shown that in peat‐bog sites active vegetation period temperature higher than the long‐term average influences the formation of radial increment positively (r = 0.22–0.34; p